Variation at the melanocortin 4 receptor gene and response to weight‐loss interventions in the diabetes prevention program. (25th June 2013) - Pan, Qing; Delahanty, Linda M.; Jablonski, Kathleen A.; Knowler, William C.; Kahn, Steven E.; Florez, Jose C.; Franks, Paul W.; ,
Abstract : Objective: To assess associations and genotype × treatment interactions for melanocortin 4 receptor ( MC4R ) locus variants and obesity‐related traits. Design and Methods: Diabetes prevention program (DPP) participants ( N = 3, 819, of whom 3, 356 were genotyped for baseline and 3, 234 for longitudinal analyses) were randomized into intensive lifestyle modification (diet, exercise, weight loss), metformin or placebo control. Adiposity was assessed in a subgroup ( n = 909) using computed tomography. All analyses were adjusted for age, sex, ethnicity and treatment. Results: The rs1943218 minor allele was nominally associated with short‐term (6 month; P = 0.032) and long‐term (2 year; P = 0.038) weight change. Eight SNPs modified response to treatment on short‐term (rs17066856, rs9966412, rs17066859, rs8091237, rs17066866, rs7240064) or long‐term (rs12970134, rs17066866) reduction in body weight, or diabetes incidence (rs17066829) (all P interaction < 0.05). Conclusion: This is the first study to comprehensively assess the role of MC4R variants and weight regulation in a weight loss intervention trial. One MC4R variant was directly associated with obesity‐related traits or diabetes; numerous other variants appear to influence body weight and diabetes risk by modifying the protective effects of the DPP interventions.